Maintenance Methodologies Embraced for Railroad Systems: A Review - Priyanka Prabhakaran; Anandakumar Subbaiyan; Dineshkumar Gopalakrishnan; Harsha Vardhana Balaji.M; S. Ramkumar; Suresh Veluswamy; Dinesh Kumar Murugesan; Satheeshkumar Seerangagounder; Sivakumar Arunachalam; Prabhu Velusamy; Priyanka Bhaskaran (Advances in Materials Science and Engineering)
Congestion on land, hike in fuel costs, and critical need to cut down environmental emissions have generated the urge to shift from conventional rail transit systems to metro rail and high-speed rail for a mass mode of transportation. The conventional railway network especially in India stages an effective space in the means of mass transit systems. Subsequently, periodic inspection of the state of railway tracks is vital for ensuring rail safety, as tracks are critical components of train transportation networks. Tracks are designed to withstand zero critical incidents, and with the advent of new high-speed train services, there is a greater need to focus on track performance. Track maintenance methods are customized to suit local conditions for enhancing safety and reducing disruptions while guaranteeing the resilience and sustainability of any rail system. In recent years, various aspects of the TMSs (track maintenance systems) have been introduced within the railway industry for both ballasted and ballastless track systems. This study reviewed various approaches to track maintenance measures using traditional methods, statistical methods, and geometry-based methods based on track deterioration. Among all the reviewed methods, track maintenance based on the geometry is said to cater to the needs of the maintainers. The outcomes of this study are expected to support and assist in track maintenance decisions in the railway industry.